2022
DOI: 10.1183/23120541.00183-2022
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in Mexico City during the COVID-19 lockdown possibly decreased COPD exacerbations

Abstract: This manuscript has recently been accepted for publication in the ERJ Open Research. It is published here in its accepted form prior to copyediting and typesetting by our production team. After these production processes are complete and the authors have approved the resulting proofs, the article will move to the latest issue of the ERJOR online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Considering the greater variety of emission sources, the decrease in particulate air pollution was somewhat lower but still significant [1], which is similar to our findings. Mexico City experienced a statistically significant decrease in particulate air pollution during the first year of the pandemic compared to 2019 [26], while in Palermo, Italy, PM 10 concentrations decreased by 45% [27], and in Kazakhstan, the concentration of PM 2.5 decreased by 21% compared to the pre-lockdown period [28]. Analyzing the levels of air pollution during the lockdown in 278 Chinese cities, Yumin et al [7] determined a drastic reduction in all observed environmental air pollutants, with the exception of ozone (on average, PM 2.5 concentrations decreased by 14.3 µg/m 3 , PM 10 by 22.2 µg/m 3 , NO 2 by 17.7 µg/m 3 , and SO 2 concentrations decreased by 2.9 µg/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the greater variety of emission sources, the decrease in particulate air pollution was somewhat lower but still significant [1], which is similar to our findings. Mexico City experienced a statistically significant decrease in particulate air pollution during the first year of the pandemic compared to 2019 [26], while in Palermo, Italy, PM 10 concentrations decreased by 45% [27], and in Kazakhstan, the concentration of PM 2.5 decreased by 21% compared to the pre-lockdown period [28]. Analyzing the levels of air pollution during the lockdown in 278 Chinese cities, Yumin et al [7] determined a drastic reduction in all observed environmental air pollutants, with the exception of ozone (on average, PM 2.5 concentrations decreased by 14.3 µg/m 3 , PM 10 by 22.2 µg/m 3 , NO 2 by 17.7 µg/m 3 , and SO 2 concentrations decreased by 2.9 µg/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although in nearly all regions where the lockdown was implemented, the population's exposure to ambient air pollution decreased, little is known about the effects of exposure to air pollution within the indoor environments where individuals reside. Even though there are assumptions that measures implemented to prevent the spread of SARS-CoV-2 infection did not contribute to the reduction in indoor air pollution [26], one Chinese study that monitored PM 2.5 concentrations in 147 homes from 30 villages using special analyzers found that during the lockdown there was no statistically significant increase in the concentration of these particles compared to the period before the pandemic [47], whereas another Chinese study demonstrated that during the lockdown in China there was a significant increase in the PM 2.5 indoor concentrations [48]. Notwithstanding, considering the recommendation to stay indoors, it is plausible that the populace may have been subjected to prolonged exposure to certain levels of indoor air contaminants, rendering them vulnerable to the adverse consequences of air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to a decrease in intercurrent infections because of the respiratory protection measures and social restrictions imposed in many countries [3][4][5][6][7][8][9][10][11]. The reduction in industrial and urban pollution, greater therapeutic adherence or a decrease in attendance to health centers due to the overload and fear of infection may be other contributing factors to this change [3,11,12].…”
Section: Introductionmentioning
confidence: 99%